(untitled) (American Journal of Islam and Society, 2013)
To understand how the Arab Spring may evolve over the coming years, we have to understand its specific context. The “revolutions” across the Middle East are not just a product of discontent and fury against dictatorships; after all, the Arabs have been raging against their rulers for well over half a century. The Arab Spring is also a creation of a particular period of time, a time in which globalization, interconnection, and instant communication are the norm, and authority and political legitimacy are in flux. It is a period of uncertainty, ambiguity, chaotic behavior, and rapid change that I have elsewhere described as “postnormal times.”1Moreover, as Nader Hashemi has observed, “the Arab Spring is not a single event but rather a long-term process of political change. Its precipitating factors were both political and economic; and while history has yet to render its ultimate judgment, fundamental questions remain about how best to understand the nature, character, and trajectory of Arab revolts.”2 I contend that we need to grasp the context of postnormal times, which served as a catalyst for the Arab revolts and within which the long-term process of political transformation is taking place, to comprehend the dynamics of the Arab Spring and anticipate its trajectory. To appreciate the reality of contemporary times, it is important to realize that the problems of the Arab state, indeed the problems of all societies, national as well as international, are complex. The politics of a democracy, the questions of economic reforms, the hopes and aspirations of a diverse and pluralistic society, the stubbornness of entrenched institutions such as the police and the military, are all complex issues that do not have simple or straightforward answers. Complexity is enhanced by the fact that all such problems ...